2021
DOI: 10.3390/jrfm14040167
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Corporate Environment, Social and Governance (ESG) Reporting among Asian Firms

Abstract: Departing from previous studies, which have mostly focused on Western countries, our work investigates the determinants of the corporate environment, social and governance (ESG) reporting among Asian firms. Examining Asian public listed firms from 2005 to 2017, our cross-sectional model results indicate that firm characteristics (economic performance, profitability, leverage and size) are found to disclose additional ESG information. The outcome is consistent with the legitimacy theory, which posits that firms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(78 citation statements)
references
References 53 publications
3
35
1
Order By: Relevance
“…As Rahman and Alsayegh (2021) point out, no generally accepted theory explains corporate voluntary disclosure practices, but it can be argued that the legitimacy theory is currently dominant in the ESG literature. It is used to explain or predict particular sustainability reporting practices by managers (Dyduch and Krasodomska, 2017;Gray et al, 1995;Hooghiemstra, 2000;Rahman and Alsayegh, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…As Rahman and Alsayegh (2021) point out, no generally accepted theory explains corporate voluntary disclosure practices, but it can be argued that the legitimacy theory is currently dominant in the ESG literature. It is used to explain or predict particular sustainability reporting practices by managers (Dyduch and Krasodomska, 2017;Gray et al, 1995;Hooghiemstra, 2000;Rahman and Alsayegh, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…As Rahman and Alsayegh (2021) point out, no generally accepted theory explains corporate voluntary disclosure practices, but it can be argued that the legitimacy theory is currently dominant in the ESG literature. It is used to explain or predict particular sustainability reporting practices by managers (Dyduch and Krasodomska, 2017;Gray et al, 1995;Hooghiemstra, 2000;Rahman and Alsayegh, 2021). Suchman (1995: 574) stated that legitimacy theory could be defined as a generalized perception or assumption that the actions of an entity are desirable, proper, or appropriate within some socially constructed system of norms, values, beliefs, and definitions.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The last-mentioned theory (legitimacy) is perhaps the most frequently associated in the literature precisely with the aspect of ESG disclosures. Given that our previous article discusses it in more detail, we will only synthetically mention that it is used to explain particular sustainability reporting practices by managers and allows for a generalized perception or assumption that the actions of an entity are desirable, proper, or appropriate within some socially constructed system of norms, values, beliefs, and definitions (Dyduch and Krasodomska, 2017;Hooghiemstra, 2000;Meek et al, 1995;Rahman and Alsayegh, 2021;Suchaman, 1995). The literature further highlights that ESG disclosures respond to societal needs (and even public pressure) in this regard (Hahn and Kühnen, 2013;Rahman and Alsayegh, 2021).…”
Section: The Impact Of Esg Reporting On the Cost Of Capital: An Example Of Us Healthcare Entities 682mentioning
confidence: 99%
“…Given that our previous article discusses it in more detail, we will only synthetically mention that it is used to explain particular sustainability reporting practices by managers and allows for a generalized perception or assumption that the actions of an entity are desirable, proper, or appropriate within some socially constructed system of norms, values, beliefs, and definitions (Dyduch and Krasodomska, 2017;Hooghiemstra, 2000;Meek et al, 1995;Rahman and Alsayegh, 2021;Suchaman, 1995). The literature further highlights that ESG disclosures respond to societal needs (and even public pressure) in this regard (Hahn and Kühnen, 2013;Rahman and Alsayegh, 2021). It is indicated that stakeholders put increasing pressure on companies to prove that they operate sustainably, reduce negative environmental and social impacts, and implement sustainability measures (Eliwa et al, 2019;Manes-Rossi et al, 2020;Raimo et al, 2021).…”
Section: The Impact Of Esg Reporting On the Cost Of Capital: An Example Of Us Healthcare Entities 682mentioning
confidence: 99%